2021
DOI: 10.1002/cbdv.202100167
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Antioxidant Activity of the Aerial Part Extracts from Matthiola incana subsp. rupestris and subsp. pulchella (Brassicaceae) Endemic to Sicily

Abstract: As part of a project aimed at investigating the Matthiola taxa endemic to Sicily (Italy), this study focused on Matthiola incana, an edible species used in the traditional medicine of various countries. Herein, the characterization of phenolic and volatile compounds, the antioxidant capacity in vitro (1,1-diphenyl-2picrylhydrazil (DPPH), reducing power and Fe 2 + chelating activity assays) and the toxicity test (Artemia salina lethality bioassay) of the hydroalcoholic extracts from the aerial parts of M. incan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent research focused on the characterization of the active chemical components and biological applications of the extracted plants of the Matthiola genus. The different extracts of Matthiola species were stated to exhibit various biological activities such as antioxidant, neuroprotective, antimicrobial, antiparasitic, antiurolithiatic, insecticidal, anticancer, and allelopathic activities [10][11][12]. Chemically, many studies concerning the chemical constituents of the Matthiola genus revealed the presence of isothiocyanate, anthocyanins, glucosinolates, flavonoids, lipids, sterol glycosides, and volatile oils [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research focused on the characterization of the active chemical components and biological applications of the extracted plants of the Matthiola genus. The different extracts of Matthiola species were stated to exhibit various biological activities such as antioxidant, neuroprotective, antimicrobial, antiparasitic, antiurolithiatic, insecticidal, anticancer, and allelopathic activities [10][11][12]. Chemically, many studies concerning the chemical constituents of the Matthiola genus revealed the presence of isothiocyanate, anthocyanins, glucosinolates, flavonoids, lipids, sterol glycosides, and volatile oils [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the herb Matthiola incana has been indicated to be effective as a tumorigenesis inhibitor. It should be noted that the molecular mechanism by which this plant exerts its anticancer effects, including its antioxidative stress, cytotoxic effects, and antioxidants, is not yet completely understood (30).…”
Section: Introductionmentioning
confidence: 99%